Consequential approach of Islamic Bioethics (Bangladesh Journal of Bioethics, 2012)
Bioethics is the understanding of right, responsibility, justices and moral interaction in living being. It is the corner stone to guide the society for righteous action. Due to the enormous innovation of sciences and technology, wide-ranging ethical issues have been raised in biotechnology, nanotechnology, assisted reproductive technologies (ART) and stem cell research. These advancements could lead to irreversible disasters if not limited by ethical principles and similarly society can not gain the benefit from this new technology if not addressed by the philosophical reflection. To date few attempts appear to have been made at a critical interpretation of the philosophical reflection on Islamic bioethics. This article shows that the Islamic medical ethics is a virtue ethics, deontological ethics (moral duties and obligations) and a consequential approach. It may help the health professionals, educator and the policy maker to get insight the knowledge of new application of ART in their practice for the welfare of the society. DOI: http://dx.doi.org/10.3329/bioethics.v3i1.10868 Bangladesh Journal of Bioethics 2012; 3(1):19-22